Characterising the impact of rainfall on dustfall rates - J. Lodder (Clean Air Journal, 2016)
Soil moisture increased the cohesion potential between particles, reducing the ability of the particle to be entrained. Dust suppression techniques are designed to increase soil moisture and therefore soil cohesion through the application of water or water-based chemicals to surfaces that have known potential for dust entrainment. Rainfall has the ability to act as a natural dust suppression mechanism; however, there is a paucity of literature on the actual effectiveness of rainfall in this regard. The ASTM D1739 methods for dustfall monitoring, commonly used in South Africa, and the National Dust Control Regulations (2013), both state that rainfall should be recorded when conducting dustfall monitoring. The rationale is that rainfall or the absence thereof, results in lower or higher dustfall rates, respectively. A suitable study site was identified in Mpumalanga, South Africa. This site had eight non-directional dustfall samplers in the near vicinity of an air quality monitoring station. Dustfall results from the eight samplers were analysed based on four scenarios, two that considers the presence of rainfall and two that consider the absence of rainfall. This analysis was further combined with wind speed data. This study, over a 24-month period indicates that there is no substantial evidence that above average rainfall will result in below average dustfall. This occurred for one month out of 24 months. Conversely, there is no consensus that the absence of rainfall will result in higher dustfall rates, which occurred cumulatively 30% of the time. Additional environmental and / or operational information may have a greater influence on dustfall compared to rainfall. Careful consideration should be taken to prevent misrepresentation of causational effects of rainfall on dustfall results. Management of dust should be undertaken through dust mitigation measures irrespective of the natural rainfall regime.